The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/2979780
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Perioperative Auricular Therapy on Postoperative Pain after Total Hip Arthroplasty: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: Auricular therapy (AT) is a conventional therapy in traditional Chinese medicine. However, the effectiveness of perioperative AT in pain treatment after total hip arthroplasty (THA) is still controversial. Nine randomised controlled trials (RCTs) involving 605 patients who have undergone THA with or without AT from inception to March 2018 were collected and included in this study by searching more than 12 databases (e.g., PubMed, Excerpta Medica Database, and Cochrane Library). A random-effects model that pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Auricular therapy is a conventional therapy in traditional Chinese medicine, and its effect is gradually recognized. Since the 1980s, studies in auricular therapy for pain management have increased [8][9][10][11][12], such as for perioperative pain [11,13,14], dysmenorrheal [15][16][17], arthralgia [18], and cancer pain [19]. In order to gather and evaluate the efficacy and safety of auricular therapy for cancer pain, we conducted this systematic review and metaanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Auricular therapy is a conventional therapy in traditional Chinese medicine, and its effect is gradually recognized. Since the 1980s, studies in auricular therapy for pain management have increased [8][9][10][11][12], such as for perioperative pain [11,13,14], dysmenorrheal [15][16][17], arthralgia [18], and cancer pain [19]. In order to gather and evaluate the efficacy and safety of auricular therapy for cancer pain, we conducted this systematic review and metaanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its safety and effectiveness, as well as negligible side effects, it is receiving increasing acceptance by physicians and patients. Up till now, a great number of modern studies have indicated that AT is an effective therapy in the management of various types of painful conditions [42][43][44][45][46][47][48][49]. Nevertheless, the exact mechanisms underlying AT for treating pain remain inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited mention in best practice guidelines,10 CM therapies, when integrated with traditional techniques, have been shown to have added benefit in the treatment of perioperative pain (table 1). For example, perioperative acupuncture, including full-body, auricular, and transcutaneous electrical therapy, has been shown to reduce both intraoperative and postoperative opioid use 11–17. But less invasive techniques such as music therapy, aromatherapy, and therapeutic suggestion (eg, providers make positive statements such as ‘you will wake up feeling well’) also have evidence suggesting their ability to reduce perioperative pain and opioid use 18–23.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the doses of these agents, the associated side effects and the resources expended to treat these side effects may also be reduced. For example, studies of perioperative acupuncture have reported a reduced incidence of postoperative nausea and delirium, decreased frequency of postoperative antiemetic use, and shorter times to extubation and discharge from the recovery room 11–17 27–29. Furthermore, studies suggest that CM therapies may also mitigate the body’s overall response to the stress of surgery 26.…”
Section: Discussionmentioning
confidence: 99%